Metabonomics reveals that entomopathogenic nematodes mediate tryptophan metabolites that kill host insects - Zhang, Yuan; Wang, Fang; Zhao, Zihua (Frontiers in Microbiology, 2022)
The entomopathogenic nematode (EPN) Steinernema feltiae, which carries the symbiotic bacterium Xenorhabdus bovienii in its gut, is an important biocontrol agent. This EPN could produce a suite of complex metabolites and toxin proteins and lead to the death of host insects within 24-48 h. However, few studies have been performed on the key biomarkers released by EPNs to kill host insects. The objective of this study was to examine what substances produced by EPNs cause the death of host insects. We found that all densities of nematode suspensions exhibited insecticidal activities after hemocoelic injection into Galleria mellonella larvae. EPN infection 9 h later led to immunosuppression by activating insect esterase activity, but eventually, the host insect darkened and died. Before insect immunity was activated, we applied a high-resolution mass spectrometry-based metabolomics approach to determine the hemolymph of the wax moth G. mellonella infected by EPNs. The results indicated that the tryptophan (Trp) pathway of G. mellonella was significantly activated, and the contents of kynurenine (Kyn) and 3-hydroxyanthranilic acid (3-HAA) were markedly increased. Additionally, 3-HAA was highly toxic to G. mellonella and resulted in corrected mortalities of 62.50%. Tryptophan metabolites produced by EPNs are a potential marker to kill insects, opening up a novel line of inquiry into exploring the infestation mechanism of EPNs.